2023
DOI: 10.1080/15476278.2022.2164159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manufacturing of Regulatory T Cell Products For Adoptive Cell Therapy and Strategies to Improve Therapeutic Efficacy

Abstract: Based on successes in preclinical animal transplant models, adoptive cell therapy (ACT) with regulatory T cells (Tregs) is a promising modality to induce allograft tolerance or reduce the use of immunosuppressive drugs to prevent rejection. Extensive work has been done in optimizing the best approach to manufacture Treg cell products for testing in transplant recipients. Collectively, clinical evaluations have demonstrated that large numbers of Tregs can be expanded ex vivo and infused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…It has been reported that stimulation of Tregs with anti‐CD3/CD28, rapamycin, or retinoic acid increases their proliferation and enhances their regulatory capacity, which could improve their function in the treatment of autoimmune diseases or transplant rejection. 34 This suggests that activation of the suppressive immune response is required to promote a neuroprotective effect of regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that stimulation of Tregs with anti‐CD3/CD28, rapamycin, or retinoic acid increases their proliferation and enhances their regulatory capacity, which could improve their function in the treatment of autoimmune diseases or transplant rejection. 34 This suggests that activation of the suppressive immune response is required to promote a neuroprotective effect of regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…ATregCT therapy involves the isolation of Tregs from patients, followed by an ex vivo expansion of the cells prior to their autologous transference [69,77]. Tregs used in ATregCT are typically isolated from peripheral mononuclear blood cells (PMBCs) using magnetic or Resident DCs in mucosal tissues participate in the generation and maintenance of FoxP3 + Tregs as well as other subtypes of Tregs through mechanisms that are dependent on IL-27, TGF-β, IL-10, RA, indoleamine-2,3-dioxygenase and vitamin D [65].…”
Section: Adoptive Treg Cell Transfer Therapy: An Overviewmentioning
confidence: 99%
“…ATregCT therapy involves the isolation of Tregs from patients, followed by an ex vivo expansion of the cells prior to their autologous transference [69,77]. Tregs used in ATregCT are typically isolated from peripheral mononuclear blood cells (PMBCs) using magnetic or fluorescence activated cell sorting with relevant antibody panels [78].…”
Section: Adoptive Treg Cell Transfer Therapy: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation